PERKEMBANGAN MANUSIA-ANAK DALAM AL-QUR’AN DAN AL-HADITS: Perkembangan Manusia Dalam Perspektif Islam - Rosyidah, Neneng Aida; Nurkhairina, Nurkhairina; Sauri, Rohmat (Staisman Press, 2024)
The Al-Qur’an adan Al-Hadits are the life guidelines for muslims in the world. Guidance in carrying out the flow of life. Every event in this world has it solution. Even thought the Al-Qur’an and Al-Hadits are the books of muslims, every human being in the world is allowed to take lessons from them to carry out activities in their lives and solve the problem they face. One thing written in the Qur’an and Hadits is related to human-child development. So far there are not many studies that discuss child development using an Islamic perspective. More often discussingpshychology whoes theories are bassed on weatern psychology. So it sounds strange when discussing child development from an Islamic perspective. This paper presents studies related to the concept of children in islam (Al-Qur’an and Al-Hadits). Child development in islam(Al-Qur’an and Al-Hadits ) and patterns of child care and education from an Islamic perspektive. Search for information data in this paper using library research. Data collection is carried out by looking for material studies related to the discussion which is then analyzed. The findings showed that children’s development in the Al-Quran and Al-Hadits was discussed by providing strict boundaries. The most important training pattern so that children can act as Khalifatullah on erth and also as Abdullah”is to educate children based on the Qur’an and Hadith.